Performance of recycling aggregate self-compacting concrete incorporating supplementary cementitious materials: an overview - Aljamala, Said Mohammed Mostafa; Safiee, Nor Azizi; Mohd Nasir, Noor Azline; Abdul Aziz, Farah Nora Aznieta (Universiti Putra Malaysia Press, 2025)
Since the construction industry expands, the demand for environmentally friendly construction approaches becomes more urgent to preserve the environment and limited natural resource reserves. In the context of current concrete manufacturing, one of the primary issues with self-compacting concrete is its high cement requirement. Recent studies estimate that cement manufacturing contributes to at least 8% of worldwide carbon dioxide (CO₂) emissions. Using supplementary cementitious materials (SCMs), including silica fume (SF), ground granulated blast furnace slag (GGBS), fly ash (FA) and metakaolin (MK), is an alternate approach to reduce CO₂ emissions associated with concrete production. Cementitious and pozzolanic materials have been widely employed as SCMs to partially replace cement as a binding agent in concrete. Recycling accumulated construction waste, such as concrete aggregate, is a promising approach to reduce the adverse environmental impact and meet the growing global demand for raw resources. However, unlike natural aggregate (NA), recycled concrete aggregate (RCA) does not exhibit appropriate structural performance due to its inferior material qualities. This article intends to provide a review of the recent research on SCM in producing recycled concrete aggregate self-compacting concrete (RCA-SCC) with respect to its fresh and mechanical properties. Incorporating SCMs like FA, GGBS, and SF in RCA-SCC enhances workability. Ternary mixes, especially with FA and GGBS, demonstrate improved sustainability and workability compared to binary mixes. Using SCMs is suggested to improve the quality of RCA and the interfacial transition zones (ITZ), potentially enhancing mechanical properties.